Stress and coping in families - Maguire, Katheryn C. (Key themes in family communication, 2012)
Synthesizes literature from a wide variety of disciplines to examine family interaction in the context of stressful situations. Designed as a textbook within Polity?s Key Themes in Family Communication series. Looks at the topic of stress and coping across the individual, relational and family levels